AMELIORATIVE EFFECT OF EUGENOL AND ANETHOLE ON ARSENIC INDUCED OXIDATIVE DNA DAMAGE IN CULTURED HUMAN PERIPHERAL BLOOD LYMPHOCYTES (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Arsenic contamination is one of the major health concerns all over the world and associated with various types of cancer and pathological effects. The production of reactive oxygen species (ROS) plays a crucial role in arsenic mediated toxicity. Several studies have shown that population constantly exposed to arsenic have substantial oxidative stress that, in turn, induces DNA damage. In the present work eugenol and anethole were investigated for their protective effect against arsenic mediated oxidative DNA damage in peripheral blood lymphocytes. Comet assay and lipid peroxidation was used as biomarker of genotoxicity and oxidative stress respectively. A dose dependent increase in tail moment and lipid peroxidation was observed when lymphocytes were treated with sodium arsenite. Treatment of arsenic (50µM) along with eugenol (20µM) and anethole (50µM) showed a significant decrease in the tail moment and lipid peroxidation in cultured peripheral blood lymphocytes. The decrease in the tail moment and lipid peroxidation was significantly higher in combined supplementation of eugenol and anethole as compared to individual administration. The results of the present study suggests ameliorative role of eugenol and anethole against arsenic induced genotoxic and oxidative damage in cultured human peripheral blood lymphocytes.